2017
DOI: 10.3389/fpsyg.2017.00516
|View full text |Cite
|
Sign up to set email alerts
|

Connections of Grasping and Horizontal Hand Movements with Articulation in Czech Speakers

Abstract: We have recently shown in Finnish speakers that articulation of certain vowels and consonants has a systematic influence on simultaneous grasp actions as well as on forward and backward hand movements. Here we studied whether these effects generalize to another language, namely Czech. We reasoned that if the results generalized to another language environment, it would suggest that the effects arise through other processes than language-dependent semantic associations. Rather, the effects would be likely to ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 29 publications
(51 reference statements)
0
10
0
Order By: Relevance
“…This articulation-movement effect was observed even though the participants were not required to explicitly process the frontness/backness dimension of the vowel, they were entirely unaware about the objectives of the study, and most of them did not even know that, for example, [i] is more a frontal vowel than [o]. Moreover, we have more recently observed the same effect in Czech speakers (Tiainen, Lukavský, Tiippana, Vainio, Šimko, Felisberti & Vainio, 2017). These studies suggest that people have an implicit and language-independent tendency to link forward hand movements with front-close vowels and backward hand movements with back-open and back-mid-open vowels.…”
Section: Introductionmentioning
confidence: 66%
“…This articulation-movement effect was observed even though the participants were not required to explicitly process the frontness/backness dimension of the vowel, they were entirely unaware about the objectives of the study, and most of them did not even know that, for example, [i] is more a frontal vowel than [o]. Moreover, we have more recently observed the same effect in Czech speakers (Tiainen, Lukavský, Tiippana, Vainio, Šimko, Felisberti & Vainio, 2017). These studies suggest that people have an implicit and language-independent tendency to link forward hand movements with front-close vowels and backward hand movements with back-open and back-mid-open vowels.…”
Section: Introductionmentioning
confidence: 66%
“…Errors (i.e., the participant uttered the wrong speech unit or did not produce any response) and RTs more than two standard deviations from each participant's condition means were excluded from the reaction time analysis . It is noteworthy that a 2 SD cutoff procedure is a valid and frequently used statistical tool (Singh, ) that we have previously used in all our studies that have measured reaction times of manual and vocal responses (e.g., Tiainen, Lukavský, et al, ; Vainio, Rantala, et al, ; Vainio et al, ; Vainio, Tiainen, et al, ). Of the trials, 2% were removed as errors and 4.4% were removed as outliers.…”
Section: Resultsmentioning
confidence: 99%
“…Experiment 1 showed that even though the unvoiced consonants of [t] and [k] are connected to the precision and power grips, respectively (Tiainen, Lukavský, et al, ; Vainio et al, ), their pronunciation is not influenced by the categorization of objects whose size is congruent with these grip types. That is, a statistically significant interaction between Size and Response was missing in the consonant data.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations